Creative Economic Development Strategy of Riau Province Community In As-Syatibi Shariah Maqasid Perfective (Universitas Islam Negeri Raden Intan Lampung, 2025)
Creative economy is an effort to optimize natural resources with creativity and innovation so as to produce the unique products and renewable in an effort to increase capacity building of local human resources. This study aims to analyze the strategy of developing the creative economy of the people of Riau province in the views of maqasid shariah. ANP analysis shows that there are two criteria for problems and solutions in creative economy development, namely internal problems and external problems. The results of this study indicate that the creative economy development strategy of the people of Riau province is still not optimal, marked by various problems that exist in the creative economy development strategy carried out by the Riau regional government. External problems dominate government policies, participation of related institutions, participation and support from public awareness.